Construction of an optically transparent thin-layer-electrode cell for use with oxygen-sensitive species in aqueous and nonaqueous solvents - Pilkington, M; Coles, B; Compton, R (1989)
We present a design for a reusable optically transparent thin-layer-electrode (OTTLE) cell, which is easy to assemble and does not require technical skills or services. All the complex parts are obtainable as standard items from the manufacturers quoted (vide infra). Designs for 02-free nonaqueous OTTLE cells have appeared in the literature (1-8). However, unlike the cell reported here, these all required instrument-making facilities for construction. The cell can be reused without dismantling for either aqueous or nonaqueous work. Leakage is not a problem over the lifetime of several experiments, and an additional advantage is the ability to thermostat the cell (0-40 "C).